From Games to Gambling: An Exploratory Study of Tongan-born and New Zealand-born Male Perceptions and Experiences of Gambling and Problem Gambling in New Zealand - Fehoko, Edmond Samuel (Auckland University of Technology, 2020)
In the early 1990s, Pacific peoples in New Zealand were four to six times more at risk of developing problem-gambling behaviours than the general population. Almost 30 years on, Pacific peoples continue to be more at risk than the general population, despite increasing public health efforts and treatment service provisions introduced to address this social and health issue. In looking at why this is so, my first concern was to ask why the delivery of the prevailing gambling-focussed programmes was not influencing Pacific gambling behaviours. In seeking to answer this question, it became clear that while there was a significant amount of statistical data on Pacific gambling behaviours, there was little on factors which might contribute to Pacific peoples to being at risk of developing problem-gambling behaviours, such as the place and endurance of Pacific cultural values, aspirations and, their daily family life experiences in New Zealand today. Hence, the need for this qualitative study. Given the diversity of New Zealand’s Pacific population, I decided that an ethnic-specific approach would enable a more in-depth study and that the focus should be Tongan males, given their central place in Tonga’s hierarchical and monarchical systems and as head of the family, and their role in holding and passing on family knowledge. The aims of this qualitative study were to explore Tongan male perceptions and experiences of gambling and to identify how their attitudes to gambling and problem-gambling behaviours were learnt, including and determining the importance of intergenerational transfer. The research design was interpretivist/ constructivist and phenomenological through the lens of a Tongan worldview. To capture the nature of intergenerational transfer, participants comprised of two groups – elders who had been born in Tonga and migrated to New Zealand, and New Zealand-born Tongan youth. Recruitment of participants was through snowball sampling from churches, kava-drinking circles and other community spaces. A total of 28 elders and 18 youth participated through focus group talanoa and individual talanoa. These were in Tongan or English as appropriate, and audio-recorded and transcribed by me. This study employed the descriptive thematic analysis drawing on components of Interpretative Phenomenological Approach. The first and overarching findings confirmed that there is no Tongan term for gambling nor, for problem gambling. At the same time, both elders and youth gave many instances of positive and negative outcomes and also examples of what would be classified as gambling through ‘activities’ and ‘acts’. Notably, among the participants, there were five Mātu’a and two To’utupu who did not engage in gambling activities due to gambling being a ‘waste of money’ and because of the problem-gambling behaviours of family members. The Mātu’a associated gambling with social and communal purposes, such as recreation and socialising together, with elements of competition and pride in winning also playing a large role here. Their initial gambling participation was through card games with their parents and other family members in Tonga. Over time, new forms evolved which included the exchange of cash and goods for example. However, in the early days, the purpose of these activities was mainly directed to supporting community initiatives, such as churches and village fundraisers. On migration to New Zealand, their earlier introduction to gambling was amplified through horse race betting at the TAB, mainly as a social occasion with other Tongans. For the To’utupu, gambling behaviours were learnt at home through social activities such as card games before being increased in schools, in workplaces, and in the online and technology space. Almost all To’utupu commented on their initial gambling activity through card games at home with family members. The majority of the To’utupu associated gambling with the need to win money as a quick fix and with being an easy way to win money. Gambling was also associated with status enhancement to maintain social status in their family and wider society. This study coins a new concept within the gambling and problem-gambling literature that I have called ‘cultural gambling’, which leads to the identification of status enhancement as a reason why Pacific peoples may be more at risk of developing problem-gambling behaviours. This is amplified by Tonga’s monarchical, hierarchical and familial systems. The majority of the participants were not aware of any policy document or problem-gambling preventative programmes. Preventative programmes and strategies are identified, which could help to minimise gambling harm amongst Tongans and other Pacific communities. Challenges and opportunities for future research and policy design are also included.
Keywords: Gambling; Problem Gambling; Tongan males; New Zealand-born Tongan; Talanoa Research Method; Fonua Model; Traditional Games; Card Gambling; Casino Gambling; Phenomenology; Faikava